Social Discontent or Criminality? Navigating the Nexus Between Urban Riots and Criminal Activities in Gauteng and KwaZulu-Natal Provinces, South Africa (2021) - Mongale, Collin Olebogeng (Frontiers in Sustainable Cities, 2022)
Post-apartheid South Africa is characterized by the proliferation of public protests, which occur in various contexts. These include urban riots that are typically carried out by individuals who live in residential areas who are relatively politically, socially, and economically marginalized. In this perspective, the study seeks to navigate the nexus between urban riots and criminal activities in Gauteng and KwaZulu-Natal provinces of South Africa. This will be performed by looking at the recent urban violence that erupted in Johannesburg and Durban cities of South Africa following the arrest of the former president of South Africa Jacob Zuma on 7 July for contempt of court. As a result of the incarceration of Zuma, his supporters took to the streets to demand for his release, ending in protests which quickly evolved into widespread lootings, vandalism, and an outbreak of violence that denoted elements of criminality. The two provinces, Gauteng (the country's economic hub) and KwaZulu-Natal (on the east coast), bore the brunt of this violence. What began as a call for the release of Jacob Zuma transpired into something that was heavily coordinated, controlled and, to a larger extent, dangerous, and perhaps the worst post-apartheid urban riot. However, behind these riots, there are seeds of discontents that triggered these violent riots and these include: the frustrations of hungry and cold people whose prospects were already constrained by the coronavirus disease-2019 (COVID-19) pandemic, rising inequality between rich and poor, unemployment, intra-party tensions, and ANC-factionalism, including stereotypical Zulu nationalism and racial tensions in South Africa. On the other hand, the riots that occurred in both KwaZulu-Natal and Gauteng were accompanied by criminality such as looting, torching, and burning of private and public properties and, to a larger degree, murder of civilians. Findings are that the urban riots in both Gauteng and KwaZulu-Natal provinces have resulted in human (in)securities such as exacerbation of poverty, food and fuel shortages, effects on the health sector (amid the COVID-19 crisis), loss of lives, and increase in unemployment. Methodologically, the study relies on a mixed method of research and content analysis.